Controlling Size‐Dispersion of Single Walled Carbon Nanotubes by Interaction with Polyoxometalates Armed with a Tryptophan Tweezer. Issue 3 (23rd October 2018) - Syrgiannis, Zois; Trautwein, Guido; Calvaresi, Matteo; Modugno, Gloria; Zerbetto, Francesco; Carraro, Mauro; Prato, Maurizio; Bonchio, Marcella
Abstract : A bis‐tryptophan tweezer was installed on a polyoxometalate (POM) surface via a bis‐amide covalent bond, yielding the enantiopure hybrid POM with C 2 symmetry, as a result of the regioselective functionalization of decatungosilicate [γ‐SiW10 O36 ] 8– at the lacunary site. The combined polyanionic and receptor properties are instrumental for a POM‐driven solubilization and enrichment of single walled carbon nanotubes (SWCNTs) with diameter <1.1 nm, as demonstrated by Raman and UV/Vis‐NIR evidence, in agreement with the calculated energetics of the tryptophan tweezer–SWCNT interaction. Abstract : The preference of SWCNT(9, 3) to interact within a tryptophan‐based hydrophobic pocket is demonstrated by experimental and computational evidence, addressing the selective binding of a polyoxometalate‐based tweezer